2011
DOI: 10.1002/j.2050-0416.2011.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Low Molecular Weight Peptides in Chinese Rice Wine (Huang Jiu) by UPLC-ESI-MS/MS

Abstract: The aim of this work was to increase the general knowledge of peptide identification and to examine the low molecular weight peptides in Chinese rice wine (Huang Jiu) as there are very few publications in the literature on this topic. Chinese rice wine (Huang Jiu) has a high content of peptides and more than 500 peptides have been tentatively identified by ultra-performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-ESI-MS/MS), including 43 potential bioactive peptides and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 39 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…The proteins that are rich in proline are also responsible for producing haze (turbidity) in beer by combining with polyphenols . The presence of these amino acids indicates the presence of low molecular weight peptides in the rice beer, with bioactive and sensory active properties as described by Han and Xu .…”
Section: Discussionmentioning
confidence: 67%
“…The proteins that are rich in proline are also responsible for producing haze (turbidity) in beer by combining with polyphenols . The presence of these amino acids indicates the presence of low molecular weight peptides in the rice beer, with bioactive and sensory active properties as described by Han and Xu .…”
Section: Discussionmentioning
confidence: 67%
“…Regarding R 2 , a higher value indicates better correlation between actual and predicted data. The value of R 2 for Eqn (7) was 0.9671, suggesting that 96.71% of the total variables could be predicted by the model. The model can be proved fit, and adequately account for the variation observed, if the F-test for the model is significant at P < 0.05.…”
Section: Model Fitting and Statistical Analysismentioning
confidence: 96%
“…This traditional technique brings a unique flavor to Chinese rice wine . Another conspicuous characteristic is that Chinese rice wine has good nutritional value, being abundant in amino acids, oligosaccharides, vitamins, mineral elements and other ingredients . Among these is that Chinese rice wines possess antioxidant activities such as reducing capacity, and free radical scavenging activity, which is highly correlated with phenolic compounds in Chinese rice wine .…”
Section: Introductionmentioning
confidence: 99%
“…2 According to current research, huangjiu has been found to possess pharmacological and nutritional benets, which can be attributed to the various bioactive constituents in huangjiu. 3,4 These functional and nutritional compounds include polysaccharides, 5 peptides, 6 amino acids, 7 mineral elements, 8 g-aminobutyric acid, 9 hydroxymethylfurfural, 10 4-vinylguaiacol, 11 etc. In huangjiu, the formation of polyphenols is related to the raw materials and wheat Qu during huangjiu fermentation.…”
Section: Introductionmentioning
confidence: 99%